2008
DOI: 10.1093/jxb/erm289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chloroplastic- and extracellular-sourced ROS on high light-responsive gene expression in Arabidopsis

Abstract: The expression of 28 high light (HL)-responsive genes of Arabidopsis was analysed in response to environmental and physiological factors known to influence the expression of the HL-responsive gene, ASCOR-BATE PEROXIDASE2 (APX2). Most (81%) of the HL-responsive genes, including APX2, required photosynthetic electron transport for their expression, and were responsive to abscisic acid (ABA; 68%), strengthening the impression that these two signals are crucial in the expression of HL-responsive genes. Further, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
82
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 69 publications
10
82
1
1
Order By: Relevance
“…We suggest that this non-ROS signal is destined to activate AtrbohD and AtrbohF NADPH oxidases at the plasma membrane. The involvement of AtrbohD/F and a strong rapid accumulation of extracellular H 2 O 2 in high-light signaling has been observed (Davletova et al, 2005;Bechtold et al, 2008;Galvez-Valdivieso et al, 2009;Miller et al, 2009). As with the involvement of AtrbohD and AtrbohF in ABA signaling in guard cells (Kwak et al, 2003;Miao et al, 2006), we suggest that H 2 O 2 produced at the plasma membrane could oxidize glutathione peroxidase isoforms, which in turn would bind to and inhibit ABI1 and ABI2 in BSCs.…”
Section: Systemic Signalingsupporting
confidence: 69%
“…We suggest that this non-ROS signal is destined to activate AtrbohD and AtrbohF NADPH oxidases at the plasma membrane. The involvement of AtrbohD/F and a strong rapid accumulation of extracellular H 2 O 2 in high-light signaling has been observed (Davletova et al, 2005;Bechtold et al, 2008;Galvez-Valdivieso et al, 2009;Miller et al, 2009). As with the involvement of AtrbohD and AtrbohF in ABA signaling in guard cells (Kwak et al, 2003;Miao et al, 2006), we suggest that H 2 O 2 produced at the plasma membrane could oxidize glutathione peroxidase isoforms, which in turn would bind to and inhibit ABI1 and ABI2 in BSCs.…”
Section: Systemic Signalingsupporting
confidence: 69%
“…SRO1 expression level varies less in response to abiotic stress than RCD1, but neither gene shows large changes in expression in response to any of the abiotic stresses tested by microarray. However, RCD1 transcript has been shown to accumulate under high light stress (Bechtold et al, 2008); SRO1 transcript has not been reported to do so. This suggests that transcription or transcript stability of RCD1 may be regulated during the response to specific abiotic stresses.…”
Section: Rcd1mentioning
confidence: 96%
“…When leaves were pretreated with H 2 O 2 prior to the shift to excess excitation conditions, they developed less photooxidative damage and APX2 transcript levels, a stress marker, accumulated to lower levels (Karpinski et al, 1999). Based on these findings, H 2 O 2 was suggested to function as messenger in local and systemic signaling in response to excess light (Bechtold et al, 2008). In line with these results, H 2 O 2 transiently accumulated at t = 30 min in the L→H experiment (Figure 3), supporting its suggested role in signal transmission.…”
Section: Triggering the Ap2/erf-tf Coexpression Networkmentioning
confidence: 96%